2023
DOI: 10.1136/bmjpo-2022-001804
|View full text |Cite
|
Sign up to set email alerts
|

Use of norepinephrine in preterm neonates with dopamine-resistant shock: a retrospective single-centre cross-sectional study

Abstract: BackgroundNorepinephrine (NE) is recommended for children and full-term neonates (born at >37 gestational weeks) with septic shock. Meanwhile, data on the effectiveness of NE in preterm neonates are still limited. This study aimed to evaluate the clinical efficacy of NE in preterm neonates with dopamine-resistant shock compared with that in full-term neonates.MethodsThis was a single-centre, retrospective (January 2010–December 2020) cohort study of neonates with persistent shock despite adequate fluid resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A prospective observational study of 22 late preterm and term neonates with refractory septic shock demonstrated that NE increased systemic AP and urine output, and decreased blood lactate levels, indicating an improvement in cardiac function and tissue perfusion [72]. The effect of NE on AP in preterm and term infants with septic shock, pulmonary hypertension, or isolated systemic hypotension was confirmed by several retrospective studies which showed significant improvement in urine output, arterial blood gas values, and tissue perfusion, with decreased requirements for oxygen and inotrope support [68,70,71,129,130]. The beneficial effect of NE on shock refractory to DOP and/or DOB is attributed to its combined inotropic and pulmonary vasodilatory effects [129,131].…”
Section: Norepinephrinementioning
confidence: 92%
“…A prospective observational study of 22 late preterm and term neonates with refractory septic shock demonstrated that NE increased systemic AP and urine output, and decreased blood lactate levels, indicating an improvement in cardiac function and tissue perfusion [72]. The effect of NE on AP in preterm and term infants with septic shock, pulmonary hypertension, or isolated systemic hypotension was confirmed by several retrospective studies which showed significant improvement in urine output, arterial blood gas values, and tissue perfusion, with decreased requirements for oxygen and inotrope support [68,70,71,129,130]. The beneficial effect of NE on shock refractory to DOP and/or DOB is attributed to its combined inotropic and pulmonary vasodilatory effects [129,131].…”
Section: Norepinephrinementioning
confidence: 92%